In vivo study of antimicrobial activity from fermented mature coconut water extracted with different solvent against pyricularia oryzae: a research / Mohamad Syafiq Samsu - Samsu, Mohamad Syafiq (Faculty of Plantation and Agrotechnology, 2018)
In Malaysia, rice is be classified as major crop and every year the average production of rice increase. But , the rice production are usually disturbed by the infection of major disease of rice such as rice blast disease. Rice blast disease is commonly attack to rice from fungus Pyricularia oryzae. Mostly , local farmers were using chemical method to control the disease . The uses this method can give negative impact to environment and human. By using biological control the fermented mature coconut water extracted with different solvent, it can help to reduce the rice blast disease in rice . The objective of these studies were to determine the ability fermented coconut water with different solvent and respond the different variety of rice toward fermented coconut water against rice blast disease in vivo. Thus , the mature coconut water were collected and extracted with different solvents. As a result , the extracted mature coconut water with different solvent can overcome the growth of P. oryzae in rice . Within three weeks of data collection, the development of rice blast disease lesion leaves surfaces become slower. It can be concluded that extracted fermented coconut water with different solvent can control the rice blast disease because it contain the antimicrobial activity.